Insight into understanding the performance of deep eutectic solvent pretreatment on improving enzymatic digestibility of bamboo residues. (June 2020) - Lin, Wenqian; Xing, Sheng; Jin, Yongcan; Lu, Xiaomin; Huang, Caoxing; Yong, Qiang
Highlights: Enzymatic digestibility of 76.9% was achieved for DES-pretreated bamboo residues. Changes of cellulose properties made contribute to the enzymatic digestibility. Enzymatic digestibility linearly correlated to change of physicochemical property. Abstract: Deep eutectic solvent (DES) is a promising pretreatment for improving enzymatic digestibility of lignocellulosic material by altering the physicochemical properties. However, few work has been done to quantitatively analysis the physicochemical properties changes of lignocellulosic material with enzymatic digestibility. In this work, DES pretreatment with different molar ratios of choline chloride/lactic acid was carried out on bamboo residues and respective enzymatic digestibility was investigated and linearly fitted with corresponding physicochemical features changes of the pretreated bamboo residues. Results showed that enzymatic digestibility of DES-pretreated bamboo residues was enhanced with the increasing molar ratio of choline chloride/lactic acid, which was due to DES pretreatment's ability to remove lignin and xylan, reduce the degree of polymerization of cellulose, enhance the crystallite size of cellulose, and improve cellulose accessibility. Several compelling linear correlations (R 2 = 0.6–0.9) were observable between enzymatic digestibility and these changes of physicochemical properties, demonstrating how DES pretreatment improve the enzymatic digestibility.